The conundrum of academic freedom in Africa: Can academics in contexts such as Tanzania have absolute academic freedom? - Mtawa, M. N.; Kahangwa , G.; Ngidos, L. (South African Journal of Higher Education, 2025)
This article explores the concept and the terrain of academic freedom in Tanzania, highlighting the challenges it faces today. It goes beyond individual rights of academics to address the fundamental role universities play in critically examining power structures, societal injustices and the systems shaping our world. At the core of this issue is a persistent tension: while academics strive for unrestricted intellectual inquiry, those in authority often view critical scholarship as a threat to the established order. This dynamic stifles open dialogue, transforming universities from vibrant spaces for intellectual exchange into environments characterized by cautious conformity. To understand this phenomenon, the study looks back at Tanzania’s rich intellectual history, drawing on the experiences of academics who recall a time when critical voices and agency thrived. We conducted semi-structured interviews with a diverse group of scholars from various disciplines, career stages and genders at a Tanzanian university. This qualitative approach allowed us to delve deeply into their lived experiences and perspectives on academic freedom. Our analysis reveals a complex interplay of factors contributing to the erosion of academic freedom. Many academics expressed feelings of pressure to self-censor their research and publications, especially regarding sensitive political or social issues. In addition, a decline in university autonomy has restricted institutional capacity to protect academic freedom and foster an environment conducive to critical discourse. The diminishing presence of forums for open intellectual debates has further stifled critical scholarship and led to a shift from collective action to individual pursuits, potentially compromising the impact of academic work. In conclusion, this article calls for a renewed commitment to academic freedom in Tanzania, emphasizing the urgent need for policy and practice reforms that encourage uninhibited intellectual exploration. By restoring robust academic freedom, Tanzanian universities can become genuine pillars of knowledge creation and meaningful contributor to society’s advancement.